2009
DOI: 10.1002/chem.200802589
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide‐Based Coordination Polymers Assembled by a Flexible Multidentate Linker: Design, Structure, Photophysical Properties, and Dynamic Solid‐State Behavior

Abstract: Four picolinate building blocks were implemented into the multidentate linker N,N',N'-tetrakis[(6-carboxypyridin-2-yl)methyl]butylenediamine (H(4)tpabn) with a linear flexible spacer to promote the assembly of lanthanide-based 1D coordination polymers. The role of the linker in directing the geometry of the final assembly is evidenced by the different results obtained in the presence of Htpabn(3-) and tpabn(4-) ions. The tpabn(4-) ion leads to the desired 1D polymer {[Nd(tpabn)]H(3)O x 6 H(2)O}(infinity) (12).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 70 publications
(73 reference statements)
1
15
0
Order By: Relevance
“…Secondly, the effective concentration decreases along the lanthanide series for [ L12 b ‐2 H] 2− , whereas it increases for L2 , which produces opposite contributions to the quantities of linear over macrocyclic complexes formed along the series. This intimate dependence of the effective concentration on minor changes in the number of rotational degrees of freedom within the tridentate binding unit opens novel possibilities for rationally programming segmental ligands that favor the thermodynamic formation of discrete polynuclear complexes, or infinite coordination polymers,40 with a predetermined number of bridging ligands—a strong point for the design of single‐stranded lanthanide polymers extending along one direction and working as organic light‐emitting diodes (OLEDs) 25. Finally, both Δ E L,L and Δ E Ln,Ln may bring some additional help for the fine thermodynamic tuning of the target assemblies.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the effective concentration decreases along the lanthanide series for [ L12 b ‐2 H] 2− , whereas it increases for L2 , which produces opposite contributions to the quantities of linear over macrocyclic complexes formed along the series. This intimate dependence of the effective concentration on minor changes in the number of rotational degrees of freedom within the tridentate binding unit opens novel possibilities for rationally programming segmental ligands that favor the thermodynamic formation of discrete polynuclear complexes, or infinite coordination polymers,40 with a predetermined number of bridging ligands—a strong point for the design of single‐stranded lanthanide polymers extending along one direction and working as organic light‐emitting diodes (OLEDs) 25. Finally, both Δ E L,L and Δ E Ln,Ln may bring some additional help for the fine thermodynamic tuning of the target assemblies.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, metal organic frameworks (MOFs) composed of lanthanide ions and organic ligands, Ln-MOFs, have been widely studied. [4][5][6][7] At the present stage, various types of luminescent Ln-MOFs have been reported. MOFs provide characteristic frameworks with three-dimensional cavities that act to encapsulate metals and/or molecules (Fig.…”
Section: Introductionmentioning
confidence: 93%
“…22 Another example of an important increase of the luminescence efficiency was reported by Marchal et O significantly increases the lifetimes of the 4 F 3/2 and 4 I 13/2 excited states and the emission quantum yields. 23 A different approach to construct photoactive materials is based on novel heterometallic d-f MOFs which may simultaneously benefit from energy transfer between ligands, d-and f-block centres. In this context, Bo et al reported that [Nd(pydc) 3 Cu 3 (bipy) 3 ]Á5H 2 O and [Yb(pydc) 3 Cu 3 (bipy) 3 ]Á4H 2 O emit in the NIR at, respectively, 1060/1340 and 980 nm.…”
Section: Near-infrared (Nir) Emitting Lnmofsmentioning
confidence: 99%